2018
DOI: 10.1016/j.athoracsur.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Major Adverse Renal and Cardiac Events After Coronary Angiography and Cardiac Surgery

Abstract: Patients who had contrast-induced acute kidney injury and had cardiac surgery within 1 day of angiography had an increased risk of MARCE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…19 This study did not detect any increased incidence of acute kidney injury (AKI), but other larger scale studies that retrospectively examined patients undergoing same-day coronary angiography and any cardiac surgery (ie, not just MV surgery) have demonstrated increased risk of AKI after intravenous contrast administration. [20][21][22] These studies have found that risk of AKI is significantly decreased by waiting for at least 5 days, with one of the studies recommending a waiting period of 5 days for urgent cases, and 2 weeks for elective cases. 20 Another retrospective study examined the outcomes of PCI and MV surgery performed on separate days.…”
Section: Staged Proceduresmentioning
confidence: 99%
“…19 This study did not detect any increased incidence of acute kidney injury (AKI), but other larger scale studies that retrospectively examined patients undergoing same-day coronary angiography and any cardiac surgery (ie, not just MV surgery) have demonstrated increased risk of AKI after intravenous contrast administration. [20][21][22] These studies have found that risk of AKI is significantly decreased by waiting for at least 5 days, with one of the studies recommending a waiting period of 5 days for urgent cases, and 2 weeks for elective cases. 20 Another retrospective study examined the outcomes of PCI and MV surgery performed on separate days.…”
Section: Staged Proceduresmentioning
confidence: 99%
“…Revascularization in patients with CTO is a challenging procedure, frequently necessitating longer procedural time and larger volume of iodinated contrast [17]. The CTO procedure in some circumstances where it is part of multivessel revascularization is an alternative to coronary artery bypass surgery which has been shown to add independent additional risks to the antecedent angiographic procedure [18]. Patients undergoing percutaneous coronary intervention for CTO with pre-existing CKD may experience adverse outcomes such as AKI [19, 20] and could benefit from a risk mitigation strategy comprising screening patients for risk factors, optimizing periprocedural hydration and managing the volume of contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Tecson and colleagues in a study on 965 patients who had coronary angiography followed by cardiac surgery found that 13.1% had contrastinduced acute kidney injury; 13.8% had major adverse renal and cardiac events within 30 days and 26.2% within 1 year of surgery. They reported that patients undergoing coronary artery bypass graft surgery within one day of coronary angiography had a twofold increment in the risk of adverse cardiac and renal complications [15].…”
Section: Discussionmentioning
confidence: 99%